Reexamination of the five species of Blaberidae deposited in the Entomological Collection of the Museu Nacional/UFRJ, Rio de Janeiro, Brazil - Lopes, Sonia Maria; de Oliveira, Edivar Heeren; Khouri, Andréa (Zootaxa, 2010)
The family Blaberidae is diverse, including large wingless, brachypterous, or fully winged species. Wings of the fully winged species have many-branched veins and reach beyond the apex of the abdomen. Some species are smaller and green in color. These cockroaches are more than 40mm long; species have front femora with 1 to 3 spines on the ventroposterior margin and 1 at the tip; and lack arolia. The females of Blaberidae possess a brood sac, wherein the ootheca or loose eggs are retained until the eggs hatch (ovoviviparity). The phylogeny of roach families was explored by McKittrick (1964), Grandcolas (1994, 1996), Kambhampati (1996) and Klass (1997, 1998, 2001) (Grimaldi & Engel, 2004). We update knowledge of five species of Blaberidae from Brazil, based on a literature review and examination of the Blattaria collection in the Department of Entomology at the Museu Nacional of Rio de Janeiro, Brazil (MNRJ).